The suitability of Alagoasa extrema Jacoby (Coleoptera: Chrysomelidae: Alticinae), as a biological control agent for Lantana camara L. in South Africa - Williams, Hester Elizabeth (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2003)
Lantana camara Linnaeus (Verbenaceae), commonly known as lantana, is a highly invasive weed in many parts of the world. In South Africa it is naturalized in several provinces where it invades pastures, riverbanks, mountain slopes and valleys and commercial and natural forests, forming dense, impenetrable thickets. Chemical and mechanical control methods are expensive, labour intensive and provide only temporary relief as cleared areas are rapidly reinfested by seedlings and coppice growth. A biological control programme was initiated in South Africa in the 1960s, but despite the establishment of 11 agent species, it was considered to have had limited success. Several factors are thought to restrict the impact of the biocontrol agents. Firstly, L. camara occurs in a range of climatic regions, some of which are unsuitable for the establishment of agent species of tropical and subtropical origin. Secondly, L. camara is the result of hybridization between several Lantana species, forming a complex of hybridized and hybridizing varieties in the field, which match none of the Lantana species in the region of origin. This causes partial insect-host incompatibility, displayed as varietal preference. Thirdly, parasitism appears to have significantly reduced the effectiveness of several natural enemies. In spite of all these constraints, biological control has reduced invasion by L. camara by 26%. However, the weed is still very damaging and additional natural enemies are required to reduce infestations further. A flea-beetle species, Alagoasa extrema Jacoby (Coleoptera: Chrysomelidae), was collected from several sites in the humid subtropical and tropical regions of Mexico, and imported into quarantine in South Africa and studied as a potential biocontrol agent for L. camara. Favourable biological characteristics of this beetle included long-lived adults, several overlapping generations per year, and high adult and larval feeding rates. Observations from the insect's native range and studies in South Africa suggest that A. extrema would probably be more suited to the subtropical, rather than the temperate areas in South Africa. Laboratory impact studies indicated that feeding damage by A. extrema larvae, over a period spanning the larval stage (16 to 20 days), reduced the above-ground biomass of L. camara plants by up to 29%. Higher larval populations resulted in a higher reduction of biomass. Varietal preference and suitability studies indicated that A. extrema exhibits a degree of varietal preference under laboratory conditions, with one of the white pink L. camara varieties proving the most suitable host. This variety is one of the most damaging varieties in South Africa and is particularly widespread in Mpumalanga Province. Although A. extrema proved to be damaging to L. camara, laboratory host range trials showed it to be an oligophagous species, capable of feeding and developing on several non-target species, especially two native Lippia species (Verbenaceae). The host suitability of these species was marginally lower than that of L. camara and the potential risk to these indigenous species was deemed to be too high to warrant release. It was therefore recommended that A. extrema not be considered for release in South Africa.
Keywords: Lantana camara; Lantana camara -- South Africa; Biological pest control agents -- South Africa; Chrysomelidae